Radiotherapy instead of inguinofemoral lymphadenectomy in vulvar cancer patients with a metastatic sentinel node: results of GROINSS-V II. (1st November 2019) - Oonk, MHM; Slomovitz, B; Baldwin, P; van Doorn, H; van der Velden, J; de Hullu, J; Slangen, B; Gaarenstroom, K; Vergote, I; Brannstrom, M; van Dorst, E; van Driel, W; et al.
Abstract : Introduction/Background: Introduction: GROINSS-V II investigated whether radiotherapy is a safe alternative for inguinofemoral lymphadenectomy (IFL) in vulvar cancer patients with a metastatic sentinel node (SN). Methodology: Methods: In GROINSS-V II, a prospective multicentre phase II trial, patients were included with early-stage squamous cell carcinoma (SCC) of the vulva (diameter <4cm) without suspicious lymph nodes at imaging, who had primary surgery with SN-procedure. In case of a metastatic SN (metastasis of any size), radiotherapy was given to the groin(s) (50Gy). In case of a negative SN, patients were followed-up for ≥2 years. Stopping rules were defined for both groups to monitor groin recurrence rate. Results: From December 2005 until October 2016, 1552 eligible patients were registered. SN-metastasis occurred in 324/1552 (21%) patients. After 54 months of inclusion the stopping-rule for SN-positive patients was activated; interim analysis showed an increased risk for groin recurrence in case of SN-metastasis >2 mm and/or extranodal extension (ENE). After amendment of the protocol only patients with SN-micrometastasis ≤2 mm received radiotherapy, while those with SN metastasis >2 mm underwent IFL (with radiotherapy if >1 metastasis or ENE). Final analysis after ≥2 years of follow-up revealed six isolated groin recurrences in 157 patients with a SN-micrometastasis (3.8%). Four could not be considered radiotherapy failures: two developed recurrence in the contralateral (SN-negative) groin, two refused radiotherapy. Twenty-eight patients did not get radiotherapy (2 recurrences;7.1%). Among 129 patients who received radiotherapy to the groin(s) only two isolated groin recurrences were diagnosed (1.6%: 95%CI:0–3.8%). The combination of radiotherapy with SN was associated with minimal toxicity: 5/118(4.2%) grade 3 toxicity, no grade 4 or 5 toxicity. In 38/1222 SN-negative patients (3.1%: 95%CI:2.1–4.1%) isolated groin recurrences were diagnosed with clear protocol violations in 6 patients: incomplete treatment of the groin (n=3); primary tumor >4cm (n=1); not all SNs visualized on the lymphoscintigram removed (n=2). After exclusion of these protocol violations an isolated groin recurrence rate of 2.6% (95%CI:1.7–3.5%) was observed. Conclusion: Radiotherapy to the groins is a safe alternative for IFL in patients with SN metastasis ≤2 mm, with minimal toxicity. We further established the safety of omitting IFL in patients with SCC of the vulva <4cm and a negative SN. For patients with SN metastasis >2 mm, radiotherapy with a total dose of 50Gy was no safe alternative for IFL; dose escalation and/or chemoradiation should be investigated in these patients. Disclosure: Funded by Dutch Cancer Society.